Swimming into trouble - Ahn, Angela; Kim, Julie (Plattsburgh : Tundra, 2024)
"As a member of the Vipers Swim Team, Julia Nam's always in the pool. Mountainview Community Center is like her second home, not only because swimming at the aquatic center is her favorite thing in the world, but also because her parents run the center's sushi café. She's the youngest swimmer on the team, but definitely not the slowest. Julia can't wait for Personal Best Day - the most important day for all of the swimmers. If their times are good enough, they can enter a big regional swim meet. But then the worst thing happens. A sharp pain in Julia's ear reveals an infection and she's forbidden to swim for ten days. How can she get timed during Personal Best Day when she's not allowed in the water? Julia is desperate to get back in the pool, even if it means having to go behind her parents' backs in order to do so. But Julia's solution lands her in a sticky situation, and it's going to require the entire community center to come together to help her out of it!"--Provided by publisher.
Junior Library Guild
Ages 7-11.
Grades 2-4.
A Junior Library Guild selection (JLG)
Keywords: Ear -- Juvenile fiction. -- Infections; Swim teams -- Juvenile fiction; Swimmers -- Juvenile fiction; Time trials -- Juvenile fiction; Swim teams -- Fiction; Swimmers -- Fiction; Swim teams -- Fiction; Swimming -- Fiction